2013
DOI: 10.1039/c3cp44696d
|View full text |Cite
|
Sign up to set email alerts
|

Membrane disordering is not sufficient for membrane permeabilization by islet amyloid polypeptide: studies of IAPP(20–29) fragments

Abstract: A key factor in the development of type II diabetes is the loss of insulin-producing beta-cells. Human islet amyloid polypeptide protein (human-IAPP) is believed to play a crucial role in this process by forming small aggregates that exhibit toxicity by disrupting the cell membrane. The actual mechanism of membrane disruption is complex and appears to involve an early component before fiber formation and later component associated with fiber formation on the membrane. By comparing the peptide-lipid interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 47 publications
(126 reference statements)
2
46
0
Order By: Relevance
“…Further SSNMR studies may also directly study one of the proposed mechanisms of toxicity: the idea that oligomers disrupt the barrier function of cellular membranes [143]. This is exemplified in several existing studies that shed light on the molecular mechanism of membrane damage, by leveraging the capabilities of ssNMR to probe protein-lipid interactions and the disruption of lipid bilayer structures [52, 144, 145]. …”
Section: Discussionmentioning
confidence: 99%
“…Further SSNMR studies may also directly study one of the proposed mechanisms of toxicity: the idea that oligomers disrupt the barrier function of cellular membranes [143]. This is exemplified in several existing studies that shed light on the molecular mechanism of membrane damage, by leveraging the capabilities of ssNMR to probe protein-lipid interactions and the disruption of lipid bilayer structures [52, 144, 145]. …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] These structures disrupt the normal functioning of cells by removingt he lipid layer of membranes. [9] Furthermore, fibrillar, oligomeric and plaques tructures of various amyloids, for example,A b, b 2 -lactoglobulin, b 2 -microglobulin, and prion proteins, have provent oh ave ah ierarchical structure through studies including atomicf orce microscopy (AFM), scanning electron microscopy (SEM), cryo-electronm icroscopy (Cryo-EM), nuclear magnetic resonance (NMR) spectroscopy,a nd transmission electron microscopy (TEM). [10][11][12][13][14] Such experimental techniquesh ave revealed that oligomeric specieso fA b can form fibrillar structures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we tested IAPP clearance of POPG and DOPG vesicles, because phosphatidylglycerol is a membrane component that is widely used in the literature (37,65,66). Both hIAPP and, albeit less so, rIAPP moderately cleared light scattering from POPG more than that from DOPG, although not to the extent that they cleared POPS light scattering (as summarized in Fig.…”
Section: Iapp Transforms Negatively Charged Vesicles Into Smallermentioning
confidence: 99%